New perspectives on respiratory syncytial virus surveillance at the national level: lessons from the COVID-19 pandemic. Issue 4 (3rd April 2023) - Teirlinck, Anne C.; Johannesen, Caroline K.; Broberg, Eeva K.; Penttinen, Pasi; Campbell, Harry; Nair, Harish; Reeves, Rachel M.; Bøås, Håkon; Brytting, Mia; Cai, Wei; Carnahan, AnnaSara; Casalegno, Jean-Sebastien; et al.
The emergence of SARS-CoV-2 and the resulting coronavirus disease 2019 (COVID-19) pandemic has led to the reconsideration of surveillance strategies for respiratory syncytial virus (RSV) and other respiratory viruses. The COVID-19 pandemic and the non-pharmaceutical interventions for COVID-19 had a substantial impact on RSV transmission in many countries, with close to no transmission detected during parts of the usual season of 2020–2021. Subsequent relaxation of social restrictions has resulted in unusual out-of-season resurgences of RSV in several countries, causing a higher healthcare burden and often a higher proportion of hospitalisations than usual among children older than 1 year in age [1]. In case of an emerging infectious disease with pandemic potential, preparedness to scale up surveillance for the emerging disease while continuing the maintenance of surveillance activities of pre-existing seasonal diseases is necessary. Learning from the COVID-19 pandemic and considering the effects of this pandemic, we provide recommendations that can guide towards sustainable RSV surveillance with the potential to be integrated into the broader perspective of respiratory surveillance. https://bit.ly/40TsO0G